Pengendalian Persediaan Tablet Tambah Darah di UPT Farmasi dan Alat Kesehatan Kota Yogyakarta - Kristy Tri Wardhani (Jurnal Maksipreneur, 2016)
Women of childbearing age and pregnant women are susceptible to nutritional deficiencies of iron that can cause bleeding during childbirth. It is one of the causes of the high maternal mortality rate in Indonesia. The government, especially the Department of Health has a role in meeting the needs of the iron tablet, especially in the management of medicines. This study aims to estimate the amount of iron tablet needs for the period 2015, according to data distribution in 2013 and 2014; comparing needs iron tablet planned with the realization of the distribution in 2013 and 2014; as well as the correlations between the number of visits in the clinic by the number of prescriptions or the distribution of iron tablet needs. Quantitative research using the data distribution, transfer and planning proposals iron tablet, as well as the number of health center visits prescriptions. Data processing includes forecasting distributions based on the trend with seasonal index, forecasting needs with the method of consumption, and correlation test. The tools used are Microsoft Excel Data Analysis menu. The results of the estimated distribution in 2015 to 18 health centers with a buffer stock of 20% is 487 607 tablets that can be met from the stock early in 2015. The proportion of the distribution of the iron tablet planning for 18 health centers in 2013 was 57.48%, and in 2014 amounted to 53, 28% are caused not all pregnant women check-up and receive iron tablet in the clinic. Correlation coefficient values <0.4 indicate a weak correlation between the amount of iron tablet needs with the number of visits recipes